The East African Community Appropriation Act, 2008 - EAC (EALA, 2008)
An Act to make provision for an East African Trade Commission, the development of and East African Trade Regime, to provide for Joint Trade Negotiations and other related matters.
Pages 9 - 16
Keywords: Appropriation Act